ระบบการชำระราคาและส่งมอบหลักทรัพย์ในตลาดหลักทรัพย์ - นพวรรณ จงก้องเกียรติ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Clearing and settlement system in securities exchange is a key facility to ensure investors of legal certainty with regards to performance of obligation resulted from securities trading. At present, such system is operated by the Securities Depository Center (Thailand) Co. Ltd., which provides services of securities depository Center, (Thailand) Co. Ltd., which provides services of Securities Depository Center, clearing house and registrar under the Securities and Exchange Act B.E. 2535. Having been operating under existing framework for years, nonetheless, there remain legal uncertainties under the Act and pertinent legislation relating to services provided by the Securities Depository Center irrespective of whether its member is under receivership or reorganization or not. Such uncertainties include applicability of pari passu rule and stay, avoidance power on onerous transactions by receiving officer, cancellation of fraudulent acts and preference transfer and effect of zero hour rule on claim entitle torepayment of debt in bankruptcy or reorganization proceedings. In this thesis, the author has conducted studies concerning problems on system for clearing and settlement in securities exchange and appropriate operation together with proposed enactment of the amendment to legislation and operation in the following aspects. 1. legal enforcement of netting provision; 2. validity of clearing and settlement of securities.